Newer Oral Anticoagulants in the Treatment of Acute Portal Vein Thrombosis in Patients with and without Cirrhosis - P. Priyanka; J. T. Kupec; M. Krafft; N. A. Shah; G. J. Reynolds (International Journal of Hepatology)
Background. Newer oral anticoagulants (NOACs) are being utilized increasingly for the treatment of venous thromboembolism (VTE). NOAC use is the standard of care for stroke prophylaxis in nonvalvular atrial fibrillation and treatment of acute VTE involving extremities and pulmonary embolism. In contrast, most guidelines in the literature support the treatment of acute portal vein thrombosis (PVT) with low molecular weight heparin (LMWH) and vitamin K antagonists (VKA). Literature evaluating NOAC use in the treatment of acute portal vein thrombosis is sparse. This review focuses on the safety and efficacy of the use of NOACs in the treatment of acute PVT in patients, with or without concomitant cirrhosis, based on the most recent data available in the current literature. Methods. A systematic review was conducted through a series of advanced searches in the following medical databases: PubMed, BioMed Central, Cochrane, and Google Scholar. Keywords utilized were as follows: NOAC, DOAC (direct oral anticoagulants), portal vein thrombosis, rivaroxaban, apixaban, dabigatran, and edoxaban. Articles related to newer anticoagulant use in patients with portal vein thrombosis were included. Results. The adverse events, including bleeding events (major and minor) and the failure of anticoagulation (propagation of thrombus or recurrence of PVT), are similar between the NOACs and traditional anticoagulants for the treatment of acute PVT, irrespective of the presence of cirrhosis. Conclusions. Newer oral anticoagulants are safe and efficacious alternatives to traditional anticoagulation with low molecular weight heparin and vitamin K antagonists in the treatment of acute portal vein thrombosis with or without cirrhosis.